Peningkatan Kapasitas Aparat Kelurahan melalui Sosialisasi dan Bimtek Inovasi Pelayanan Berbasis IPTEK - Indriyati Indriyati; Yohannes Kornelius Ethelbert; Yasinta Palan Peten; Henny A. Manafe (Universitas Negeri Gorontalo, 2025)
Naimata Village Office Apparatus currently, there is a gap between the low competence of apparatus related to regional government innovation and the demands of implementing one innovation model in the implementation of public services. Therefore, a program is needed to increase the capacity of regional governments, including Village or Sub-district Governments. Community service activities through socialization and assistance of regional innovation technology at the Naimata Village Office, Kupang City, aim to increase the competence of apparatus in innovating in the field of public services. The method of implementing the activity begins with a situation analysis to map existing conditions, preparation, implementation of activities through material presentation, and interactive discussions, and ends with an evaluation. The results of the activity showed an increase in insight and knowledge of apparatus related to regional innovation. This can be measured from the understanding of regulations, definitions, types and models of regional government innovation, so that the leadership of the Naimata Village Office decided to choose digital-based population administration innovation. As a follow-up, it was agreed that periodic assistance would be provided for the implementation of the population administration service innovation.